Introduction: Exceptionalism and Necropolitical Security Dynamics in Olympic Rio de Janeiro. Issue 1 (1st June 2020) - Ystanes, Margit; Salem, Tomas
Abstract: For more than a decade, urban development in Rio de Janeiro was driven by the urgency of preparations for mega-events such as the 2014 FIFA World Cup and the 2016 Summer Olympics. During these years, Brazilian authorities used the mega-events to create a state of exception that legitimized a broad range of state security interventions across the city. While Brazilian authorities presented the events as an opportunity to create a modern, dynamic, and socially inclusive city, this special section argues that the security interventions implemented in Rio during the years of Olympic exceptionalism intensified racialized and gendered inequalities and reproduced historical patterns of necropolitical governance that has sought to render black life in Brazil impossible.